Randomized Double Blind Trial to Compare the Efficacy of Granisetron And Ondansetron in Controlling Emesis in Children with Acute Lymphoblastic Leukemia - Siddique, Rasel; Hafiz, Md Golam; Jamal, Chowdhury Yakub; Karim, Md Anwarul; Islam, Afiqul; Alia, Reema Afroza (Bangladesh Journal of Child Health, 2013)
Introduction: Nausea and vomiting are the most important side effects of cytotoxic chemotherapy and it is reported by the patients who receive chemotherapy for malignancies. Ondansetron and granisetron (5 HT3 receptor antagonists) are effective compounds with relatively less toxicity to prevent nausea and vomiting induced by high and moderate emitogenic chemotherapy. Objective: This study was carried out to evaluate the efficacy of granisetron and ondansetron preventing chemotherapy induced nausea and vomiting (CINV). Methods: In this randomized double blind trial 60 children (4-11 years) with acute lymphoblastic leukemia (ALL) who received high dose methotrexate (HDMTX-2.5gm/ m2). Each patients received either ondansetron 4 mg or granisetron 1mg (n=30) orally half an hour before HDMTX. Nausea and vomiting were assessed based on modified Morrow Assessment of Nausea and Emesis (MANE) scale for application to the children. Results: Complete response of granisetron significantly differed from ondansetron from day 2-4 (delayed emesis) (p=0.028).Complete response to acute CINV were 90% in granisetron and 70% in ondansetron treated children (p=0.053), which was not statistically significant. No Child of granisetron group required additional dose but 16.7% children of ondanseton group required additional dose on the first day (p=0.05). Episodes of nausea found in ondansetron treated children 36.7% and in granisetron group 3.3% on day four (p=0.001). Maximum episodes of vomiting found in ondansetron treated children 33.3% and minimum episodes in granisetron group 3.3% on day 2 (p=0.003). In few cases adverse effects (headache, constipation, abdominal pain, loose motion and decreased appetite) were observed in both group of patients (p=0.999). Only in 3.3% cases anticipatory nausea and vomiting had observed. Conclusion: In conclusion, single dose oral granisetron (1mg) is superior to oral ondansetron (4mg) preventing chemotherapy induced emesis in children with ALL receiving HDMTX therapy. DOI: http://dx.doi.org/10.3329/bjch.v36i3.14272 BANGLADESH J CHILD HEALTH 2012; VOL 36 (3) : 115-121